2021
DOI: 10.3168/jds.2021-20223
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical mastitis in dairy cows in major milk-producing areas of Sri Lanka: Prevalence, associated risk factors, and effects on reproduction

Abstract: Compared with clinical mastitis, the subclinical form of mastitis (SCM) is more common and thought to cause more economic losses to the dairy industry. The current study aimed to investigate the prevalence, risk factors of SCM, and effects on reproduction of dairy cows in major milk-producing areas of Sri Lanka. A total of 1,357 cows of selected farms in 3 regions were examined in the study. California Mastitis Test was conducted for individual cows, and a score of 2 or more for any quarter without any clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 56 publications
1
5
0
1
Order By: Relevance
“…In the current study, the EC test detected a cow-level prevalence of SCM similar to that reported in another study [ 34 ] and is considered low compared to other studies in tropical regions [ 8 , 17 , 40 , 44 ]. It is stated that milk from a cow with udder inflammation is a better conductor of electrical waves than milk from a healthy cow [ 45 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the current study, the EC test detected a cow-level prevalence of SCM similar to that reported in another study [ 34 ] and is considered low compared to other studies in tropical regions [ 8 , 17 , 40 , 44 ]. It is stated that milk from a cow with udder inflammation is a better conductor of electrical waves than milk from a healthy cow [ 45 ].…”
Section: Discussionsupporting
confidence: 89%
“…In another study, they found that breed and/or crossbreeding was not a risk factor in the prevalence of SCM, while the calving number (primiparous and multiparous), geographic region, and milk production (<10 L, 10–20 L or >20 L) and the region significantly contributed ( p = 0.036) to the risk of SCM. In multiparous cows, the odds of SCM were 2.51 times higher than the odds in first calving cows [ 34 ]. This information differs from the present study, where breed was a risk factor for the prevalence of SCM, with a lower risk factor in the composite breed compared to the taurus-indicus and indicus predominance studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Є суперечливі дані щодо взаємозв'язку СКМ з розвитком неплідності у корів лактаційного періоду (Dahl et al, 2017). За даними Ranasinghe et al (2021), за СКМ у корів зменшується ефективність штучного осіменіння, а тривалість днів періоду від отелення до наступного осіменіння була довшою порівняно і даними контролю (79 і 64 дні відповідно). Натомість Villa-Arcila et al ( 2017) показано, що СКМ, діагностований у перший місяць після отелення, не впливав на тривалість періоду до наступного осіменіння.…”
Section: вступunclassified
“…Mastitis is the most prevalent disease in dairy herds, consisting of mammary gland inflammation that reflects production indices and profitability of agricultural production. These factors are affected by reduced milk production (ADRIAENS et al, 2021), high costs of treatment and prevention (HE et al, 2020), and diminished reproductive performance (DAHL et al, 2020;DALANEZI et al, 2020;RANASINGHE et al, 2021).…”
Section: Introductionmentioning
confidence: 99%